Microdroplet-based multiplex PCR on chip to detect foodborne bacteria producing biogenic amines - Anna G. Sciancalepore; Elisa Mele; Valentina Arcadio; Francesco Reddavide; Francesco Grieco; Giuseppe Spano; Patrick Lucas; Giovanni Mita; Dario Pisignano (2013)
The development of fast, reliable and culture-independent molecular tools to detect bacteria producing biogenic amines deserves the attention of research and ultimately of the food industry in order to protect consumers’ health. Here we present the application of a simple, low-cost, fast and sensitive method to perform microdroplet-based multiplex PCR, directly on a food matrix, for the simultaneous detection of bacterial genes involved in biogenic amine biosynthesis. After inoculating wine with Lactobacillus brevis IOEB 9809, cell lysis and DNA amplification are performed in one single step, without preliminary nucleic acid extraction or purification treatments. The assay is performed in about 30 min, requiring 150 nL of starting sample and it enables the detection of down to 15 bacterial cells. With respect to traditional culture techniques, the speed, the simplicity and the cheapness of this procedure allow an effective monitoring of microbial cells during food-making and processing.